Serum concentration of bisphenol A in elderly cats and its association with clinicopathological findings - Kovaříková, Simona; Maršálek, Petr; Habánová, Monika; Konvalinová, Jarmila (Journal of feline medicine and surgery, 2021)
OBJECTIVES: Bisphenol A (BPA) has been mentioned as a possible factor contributing to feline hyperthyroidism. Nevertheless, there are no previous studies reporting on the concentration of BPA in feline serum and its association with thyroid function. The objectives of this study were to measure serum BPA concentration in cats aged ⩾7 years, considered as healthy by their owners, and to compare the results with clinicopathological findings. METHODS: Sixty-nine cats aged ⩾7 years considered as healthy by their owners were enrolled in the study. The concentration of BPA in feline serum was measured using liquid chromatography-tandem mass spectrometry. In all cats, signalment, living environment, diet history, and the results of haematological and biochemical analysis, including thyroxine levels, were available. RESULTS: The mean serum BPA concentration in feline serum was 1.06 ± 0.908 ng/ml. Significant correlation was found between BPA concentration and haemoglobin (r = 0.3397; P = 0.0043), haematocrit (r = 0.3245; P = 0.0065) and the number of red blood cells (r = 0.2916; P = 0.0151), concentration of total protein (r = 0.2383; P = 0.0486), concentration of calcium (r = 0.3915; P = 0.0009) and level of bilirubin (r = 0.3848; P = 0.0011). No other significant correlations were found. Significant differences (P <0.01) were found between mature (1.28 ± 0.994 ng/ml) and geriatric cats (0.420 ± 0.240 ng/ml), between strictly indoor cats (1.27 ± 0.992 ng/ml) and cats with outdoor access (0.660 ± 0.529 ng/ml), and between cats fed canned food (1.23 ± 0.935 ng/ml) and cats fed non-canned food (0.774 ± 0.795 ng/ml). CONCLUSIONS AND RELEVANCE: Measurable serum BPA levels were found in all examined samples. The age of the cats was revealed as a significant factor affecting BPA concentration and mature cats had the highest levels. A significantly higher concentration of BPA was found in cats living strictly indoors and in cats fed canned food. No association was found between BPA and thyroid function. Further studies are needed that focus on hyperthyroid cats for better evaluation of this relationship.
Keywords: fenoly; Phenols; potraviny konzervované; Animals; Cats; kontaminace potravin; Food, Preserved; senioři; zvířata; Benzhydryl Compounds; Aged; kočky; Food Contamination; benzhydrylové sloučeniny